TNF-α Enhances the Therapeutic Effects of MenSC-Derived Small Extracellular Vesicles on Inflammatory Bowel Disease through Macrophage Polarization by miR-24-3p - Huikang Xu; Jiamin Fu; Lijun Chen; Sining Zhou; Yangxin Fang; Qi Zhang; Xin Chen; Li Yuan; Yifei Li; Zhenyu Xu; Charlie Xiang (Stem Cells International)
Human menstrual blood-derived mesenchymal stem cells (MenSCs) and their secreted small extracellular vesicles (EVs) had been proven to relieve inflammation, tissue damage, and fibrosis in various organs. The microenvironment induced by inflammatory cytokines can promote mesenchymal stem cells (MSCs) to secrete more substances (including EVs) that could regulate inflammation. Inflammatory bowel disease (IBD) is a chronic idiopathic intestinal inflammation, the etiology and mechanism of which are unclear. At present, the existing therapeutic methods are ineffective for many patients and have obvious side effects. Hence, we explored the role of tumor necrosis factor α- (TNF-α-) pretreated MenSC-derived small EV (MenSCs-sEVTNF-α) in a mouse model of dextran sulfate sodium- (DSS-) induced colitis, expecting to find better therapeutic alterations. In this research, the small EVs of MenSCs were obtained by ultracentrifugation. MicroRNAs of small EVs derived from MenSCs before and after TNF-α treatment were sequenced, and the differential microRNAs were analyzed by bioinformatics. The small EVs secreted by TNF-α-stimulating MenSCs were more effective in colonic mice than those secreted directly by MenSCs, as evidenced by the results of histopathology analysis of colonic tissue, immunohistochemistry for tight junction proteins, and enzyme-linked immunosorbent assay (ELISA) for cytokine expression profiles in vivo. The process of MenSCs-sEVTNF-α relieving colonic inflammation was accompanied by the polarization of M2 macrophages in the colon and miR-24-3p upregulation in small EVs. In vitro, both MenSC-derived sEV (MenSCs-sEV) and MenSCs-sEVTNF-α reduced the expression of proinflammatory cytokines, and MenSCs-sEVTNF-α can increase the portion of M2 macrophages. In conclusion, after TNF-α stimulation, the expression of miR-24-3p in small EVs derived from MenSCs was upregulated. MiR-24-3p was proved to target and downregulate interferon regulatory factor 1 (IRF1) expression in the murine colon and then promoted the polarization of M2 macrophages. The polarization of M2 macrophages in colonic tissues then reduced the damage caused by hyperinflammation.